Radioimmunotargeting of Malignant Glioma by Monoclonal Antibody D2C7 Reactive Against Both Wild-Type and Variant III Mutant Epidermal Growth Factor Receptors - Zalutsky, Michael R. (2011)
INTRODUCTION: Malignant glioma remains a significant therapeutic challenge and immunotherapeutics might be a beneficial approach for these patients. A monoclonal antibody (MAb) specific for multiple molecular targets could expand the treatable patient population and the fraction of tumor cells targeted, with potentially increased efficacy. This motivated the generation of MAb D2C7, which recognizes both wild-type epidermal growth factor receptor (EGFRwt) and a tumor-specific mutant, EGFRvIII. METHODS: D2C7 binding affinity was determined by surface plasmon resonance and its specificity characterized through comparison to EGFRwt-specific EGFR.1 and EGFRvIII-specific L8A4 MAbs by flow cytometry and immunohisochemical analysis. The 3 MAbs were labeled with (125)I or (131)I using Iodogen, and paired-label internalization assays and biodistribution experiments in athymic mice with human tumor xenografts were performed. RESULTS: The affinity of D2C7 for EGFRwt and EGFRvIII was 5.2 × 10(9) M(−1) and 3.6 × 10(9) M(−1), and cell-surface reactivity with both receptors was documented by flow cytometry. Immunohistochemical analyses revealed D2C7 reactivity with malignant glioma tissue from 90 of 101 patients. Internalization assays performed on EGFRwt-expressing WTT cells and EGFRvIII-expressing NR6M cells indicated a threefold lower degradation of (125)I-labeled D2C7 compared with (131)I-labeled EGFR.1. Uptake of (125)I-labeled D2C7 in NR6M xenografts (52.45 ∀ 13.97% ID/g on Day 3) was more than twice that of (131)I-labeled L8A4; a threefold to fivefold tumor delivery advantage was seen when compared to (131)I-labeled EGFR.1 in mice with WTT xenografts. CONCLUSIONS: These results suggest that D2C7 warrants further evaluation for the development of MAb-based therapeutics against cancers expressing EGFRwt and EGFRvIII.